Inspirasi Harimau Sebagai Sumber Ide Busana Pesta - Sulistyadewi, Mirza Aulia; Yulistiana, Yulistiana (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
The tiger is unique in its silhouette, fur and pattern. The purpose of the research is to describe the process and find out the finished result of tiger inspiration as a source of party fashion ideas. Party dress inspired by tiger and refers to the theme of boderless cushion from Fashion Trend Forecasting Resilient 2023/2024. the inspiration is applied to manipulating fabric screen printing, slashing and embroidery. The process of making this party dress starts from extracting the source of the idea to the design process, followed by the process of making clothes and manipulating fabric. The silhouette and model in this outfit were inspired by the uniqueness of Scottish traditional clothing. The application of slashing and embroidery is found on the outer part of the women's clothing while the application of screen printing is placed on the back and front of the men's suit.